National Trends in the Burden of Atrial Fibrillation During Hospital Admissions for Heart Failure - Samuel W. Reinhardt; Fouad Chouairi; P. Elliott Miller; Katherine A. A. Clark; Bradley Kay; Michael Fuery; Avirup Guha; James V. Freeman; Tariq Ahmad; Nihar R. Desai; Daniel J. Friedman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Heart failure (HF) and atrial fibrillation (AF) frequently coexist and may be associated with worse HF outcomes, but there is limited contemporary evidence describing their combined prevalence. We examined current trends in AF among hospitalizations for HF with preserved (HFpEF) ejection fraction or HF with reduced ejection fraction (HFrEF) in the United States, including outcomes and costs. Methods and Results Using the National Inpatient Sample, we identified 10 392 189 hospitalizations for HF between 2008 and 2017, including 4 250 698 with comorbid AF (40.9%). HF hospitalizations with AF involved patients who were older (average age, 76.9 versus 68.8 years) and more likely White individuals (77.8% versus 59.1%; P<0.001 for both). HF with preserved ejection fraction hospitalizations had more comorbid AF than HF with reduced ejection fraction (44.9% versus 40.8%). Over time, the proportion of comorbid AF increased from 35.4% in 2008 to 45.4% in 2017, and patients were younger, more commonly men, and Black or Hispanic individuals. Comorbid hypertension, diabetes mellitus, and vascular disease all increased over time. HF hospitalizations with AF had higher in‐hospital mortality than those without AF (3.6% versus 2.6%); mortality decreased over time for all HF (from 3.6% to 3.4%) but increased for HF with reduced ejection fraction (from 3.0% to 3.7%; P<0.001 for all). Median hospital charges were higher for HF admissions with AF and increased 40% over time (from $22 204 to $31 145; P<0.001). Conclusions AF is increasingly common among hospitalizations for HF and is associated with higher costs and in‐hospital mortality. Over time, patients with HF and AF were younger, less likely to be White individuals, and had more comorbidities; in‐hospital mortality decreased. Future research will need to address unique aspects of changing patient demographics and rising costs.